PENGARUH PEMBENAH TANAH TERHADAP SERAPAN HARA MAKRO, KERONTOKAN DAUN, DAN HASIL CABAI LAHAN PASIR PANTAI DAERAH ISTIMEWA YOGYAKARTA PADA MUSIM HUJAN - , Anung Slamet Dwi Purwantono, Ir.,MS. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Production of chilli pepper in Indonesia is fluctuates and very seasonal, it is low in rainy season and abundant in dry season. During low season, the price increases significantly such that affects social life. Therefore, increasing chilli pepper production during rainy season is of importance to maintain production stability all year around such that chilli pepper market price is profitable for farmers while it is also affordable for consumers. A series of laboratory experiments was carried out to determine rain intensity that result in intensive nutrient leaching, and to determine the dosage of poultry manure and vertisol soil for soil amendment to improve nutrient availability. Pot experiment was carried out to know the effect of soil amendment on improvement of macro nutrient uptake in order to reduce leaves shattering, as well as improve the production of some chilli varieties at coastal sandy soil during rainy season. Observations were carried out on soil physic characteristics, nutrient availability, leached nutrients, absorbed nutrients, macro nutrients uptake, leaves shattering and chilli pepper production. The results showed that shower irrigation equal to rain intensity of 450 mm per month have caused intensive nutrient leaching on coastal sandy soil.In such intensity, macro nutrients that experienced relatively significant leaching were:NO3-N> SO4 2- > K + > Ca 2+ . Soil amendment reduced macro nutrients leaching, especially NH4-N and K + , and consequently increased macro nutrient availability so that improved macro nutrients uptake by chilli pepper plants. Sixty tonnes ha -1 poultry manure and 10% vertisol soil was the best combination to improve nutrient availability of coastal sandy soil during rainy season. Macro nutrients of N and K were the most absorbed nutrients by chilli pepper plants. Significant correlation was observed between N (r = -0.76**) and K (r = -0,74**) canopy nutrient absorption and leaves shattering, the greater the uptake the lesser the leaves shattering. Significant negative correlation was observed between leaves shattering and the yield on pot experiment, with correlation coefficientfor Red Star, Laris, Lado and TM-999were -0.76**, -0.60**, -0.66** and -0.57**, respectively. On field experiment, the coefficient of correlation for Laris was -0,61* and Lado was -0.64*. Leaves shattering on local varieties were lesser than hybrid varieties. The order of leaves shattering was Lado = TM-999 > Laris = Red Star. The order of chilli pepper yield under rainy season condition with soil amendment was Lado> TM-999 > Laris = Red Star. Compared to the control, soil amendment could increase fresh chilli fruit weight per plant of 33.63%, while plastic mulching increased fresh chilli fruit weight only 18.78%.